Analisis Tindak Tutur Direktif dalam Film “Home Sweet Loan” Karya Sabrina Rochelle Kalangie - Berliana Intan Valencia; Nila Faradila Rahmawati; Chairun Nisa; Najwa Emalia Shaputri; Zafira Nasywa Aidhina; Ardha Friska Oktalianda; Asep Purwo Yudi Utoma; Arum Yuliya Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Pragmatics is a subdiscipline of linguistics that studies the application of language in social communication by considering situational factors, the purpose of the conversation, and the status of the interlocutor. The main focus of this research is on directive speech acts. A directive speech act is a type of speech act aimed at prompting action from the speech partners by the speaker's direction. This research analyzes the directive speech acts in the movie Home Sweet Loan. A theoretical approach with pragmatic analysis and a methodological approach using a qualitative descriptive method are applied in this research. Data collection employs listening and recording techniques, utilizing the advanced technique of unparticipatory listening. The presentation of the data uses informal techniques. The results indicate a diversity of types of directive speech acts used in the dialogues of this film, including asking, ordering, suggesting, pleading, urging, commanding, advising, charging, and inviting. This finding highlights the importance of directive speech acts in sustaining communication between speakers and partners, clarifying the meaning of each interaction in the social dynamics portrayed in the film. This research contributes to a broader and deeper understanding of speech closely related to social context.